THE EFFECT OF IMPREGNATING SOLUTION CONCENTRATION ON THE CHARACTERISTIC OF ACTIVATED CARBON (UIN Mataram, 2023)
As an agricultural waste, rice husk is able to be produced as activated carbon due to its high cellulose content. This research aimed to determine the characteristics of activated carbon impregnated with zinc chloride (ZnCl2) solution at various concentrations. The activated carbon prepared from rice husk with ZnCl2 impregnation was investigated under soaking treatment. Soaking was carried out for 24 hours with ZnCl2 impregnation at various concentrations 10%, 20%, and 30%. Proximate analysis was performed on the three variations of activated carbon concentration. The best activated carbon was obtained by 30% ZnCl2 impregnation, where the moisture content was 5.08%, the ash content was 24.58%, the volatile matter content was 25.19%, and the fixed carbon content was 50.23%. Iodine number and amount of methylene blue adsorption were obtained at the maximum concentration of 30% ZnCl2 which are 631 mg/g and 322 ml/g. Impregnated activated carbon characterization test with FTIR has been carried out. The functional group is found in zinc chloride-impregnated activated carbon, consisting of OH stretching of hydroxyl groups at 3200-3600 cm-1, aromatic C=C vibrations at 1400-1600 cm-1, C=O vibration at 2300 cm-1, and C-O vibration at 1200 cm-1. Meanwhile, the absorption in band 1026 cm-1 corresponds to SiO2.